PENGARUH PENGETAHUAN KEUANGAN DAN LOCUS OF CONTROL PADA PERILAKU MANAJEMEN KEUANGAN PERSONAL (Studi Pada Mahasiswa Manajemen Keuangan Syariah Angkatan 2018 – 2020 UIN Sayyid Ali Rahmatullah Tulungagung) - Palupi, Destya Endah (PRIMA EKONOMIKA, 2022)
There must be a wide choice of products and services offered for a country with a large population like Indonesia, as well as the ability to handle financial problems. Consumptive attitudes become a habit that affects people's lifestyles, including college students. This study examines the personal financial management practices of Islamic Financial Management students at UIN Sayyid Ali Rahmatullah Tulungagung. In this study, the SPSS multiple regression model was used to collect the data. The 2018-2020 Islamic Financial Management students were used as samples. The t test, F test, and the coefficient of determination were used to test the reliability and validity of the tool and to test the hypothesis in this study. The results show that financial knowledge (X1) has no significant effect on personal financial management behavior. While locus of control (X2) has a significant influence on the personal financial management behavior of UIN Sayyid Ali Rahmatullah Tulungagung students.